ICT coverage in rural and urban basic education in Colombia-2018 - Cruz - Carbonell, Valeria; Hernández - Arias, Ángel Fabián; Silva - Arias, Adriana Carolina (Universidad Francisco de Paula Santander, 2020)
This research describes coverage and other characteristics related to access to Information and Communication Technologies (ICT)’s goods and services in educational centers located in rural and urban areas of Colombia. The universe of study was delimited to educational centers that allow access to the primary and secondary level. The data used comes from the Formal Education Census (EDUC) of the National Administrative Department of Statistics (DANE). The main objective is to highlight the inequalities related to the coverage of these goods and services in various institutions. The main findings of the research found the gaps of their implementation in education, these differences must be counteracted from the formulation and execution of educational policies that favor access to these tools, mainly in the rural sector, in order to counteract the differences in terms of quality and educational performance Colombia.